Implementation of Digital Student Worksheet Based on Problem-Solving to Enhance Students' Critical Thinking Skills and Learning Outcomes on Quantum Numbers and Electron Configuration Materials - Ratna Nilawati; Abdul Gani; Ibnu Khaldun; Putri Nabilah (Yayasan Keluarga Guru Mandiri, 2025)
In learning chemistry, especially regarding quantum numbers and electron configurations, learning difficulties are still encountered, resulting in low student learning outcomes. One of the factors contributing to this is the use of teaching materials that are less engaging and fail to facilitate students' understanding of concepts effectively. Digital-based student worksheets are an innovative alternative to learning because they can increase students' interaction, understanding of concepts, and critical thinking skills. This research aims to apply problem-solving-based digital student worksheets to improve students' critical thinking skills and learning outcomes. This research employs a quantitative approach with a quasi-experimental design, utilizing a post-test-only control group design. The research sample consisted of 72 class X students at SMA Negeri 5 Banda Aceh. The results showed that the use of digital student worksheets significantly increased students' critical thinking skills (average score of 86.96) and learning outcomes (average score of 85.3) compared to the control group (critical thinking score of 80.20 and learning outcomes of 80.33). Students demonstrated a positive response to the use of digital student worksheets, with an average questionnaire response value of 83.53. The conclusion of this study indicates that the use of digital student worksheets can enhance students' critical thinking skills and learning outcomes. The contribution of community service from this study is manifested in the provision of innovative teaching tools that teachers can adopt to improve collaborative learning and support the development of digital literacy in the school environment.